Safety of transtympanic application of probiotics in a chinchilla animal model - Carol Nhan; Aren Bezdjian; Shyamali Saha; Satya Prakash; Lily H. P. Nguyen; Sam J. Daniel (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Chronic suppurative otitis media can be recalcitrant and difficult to treat, particularly with the increasing occurrence of antibiotic resistance. Lactobacillus plantarum is a probiotic that has been shown to decrease S. aureus and P. aeruginosa growth in wounds, making it a good candidate for the treatment of chronic suppurative otitis media. However, before it can be applied in the ear, its ototoxicity potential must be evaluated. Methods A prospective controlled trial was conducted in a chinchilla animal model at the Animal care research facilities of the Montreal Children’s Hospital Research Institute to determine whether Lactobacillus plantarum is ototoxic when applied transtympanically. Ten chinchillas each had one ear randomly assigned to receive 109 CFU/mL of Lactobacillus plantarum solution, while the contralateral ear received saline. Auditory brainstem responses were measured bilaterally at 8, 20, 25 kHz before, at 7–10 days after application, and at 28 days after application of probiotic or saline. Facial nerve and vestibular function were assessed clinically. Results There were no statistically significant differences in hearing thresholds between control and experimental ears at 28 days after application. A difference of 11 dB was noted in the 25 kHz range at day 7–10, but resolved by day 28. No animals receiving probiotics developed vestibular nerve dysfunction. There was no histologic evidence of auditory hair cell damaged evidenced by scanning electron microscopy. Conclusion Our study suggests that a single application of Lactobacillus plantarum at 109 CFU/mL does not cause ototoxicity in a chinchilla animal model. These preliminary safety evaluations and the pathogen inhibitory effects of L. plantarum demonstrated by previous studies present this probiotic as a candidate of interest for further investigation.